ECONOMIC ASPECTS OF LEGAL SUPPORT FOR EMPLOYMENT IN UZBEKISTAN - Shayusupova Lobar Rikhsievna; Khasanov Azizjon Akhrol Ugli (PT ANTIS International Publisher, 2024)
This study examines the employment sector in Uzbekistan within the framework of the country's new development strategy for 2022-2026, focusing on job creation, social protection, and legislative enhancements. Drawing upon legislative frameworks such as the laws